Carnosine Supplementation Enhances Post Ischemic Hind Limb Revascularization - Boakye, Adjoa A.; Zhang, Deqing; Guo, Luping; Zheng, Yuting; Hoetker, David; Zhao, Jingjing; Posa, Dheeraj Kumar; Ng, Chin K.; Zheng, Huaiyu; Kumar, Amit; Kumar, Vijay; Wempe, Michael F.; et al. (Frontiers in Physiology, 2019)
High (millimolar) concentrations of the histidine containing dipeptide - carnosine (-alanine-L-histidine) are present in the skeletal muscle. The dipeptide has been shown to buffer intracellular pH, chelate transition metals, and scavenge lipid peroxidation products; however, its role in protecting against tissue injury remains unclear. In this study, we tested the hypothesis that carnosine protects against post-ischemic angiogenesis by augmenting HIF-1 angiogenic signaling by Fe2+ chelation. We found that wild type C57BL/6 mice, subjected to hindlimb ischemia (HLI) and supplemented with carnosine (1g/L) in drinking water, had improved blood flow recovery and limb function, enhanced revascularization and regeneration of myocytes compared with HLI mice placed on water alone. Carnosine supplementation enhanced the bioavailability of carnosine in the ischemic limb, which was accompanied by increased expression of proton-coupled oligopeptide transporters. Consistent with our hypothesis, carnosine supplementation augmented HIF1- and VEGF expression in the ischemic limb and the mobilization of proangiogenic Flk-1+/Sca-1+ cells into circulation. Pretreatment of murine myoblast (C2C12) cells with octyl-D-carnosine or carnosine enhanced HIF1- protein expression, VEGF mRNA levels and VEGF release under hypoxic conditions. Wild type C57BL/6 mice pretreated with carnosine showed enhanced blood flow in the ischemic limb following HLI surgery. In contrast, pretreatment of hypoxic C2C12 cells with methylcarcinine, a carnosine analogue, lacking Fe2+ chelating capacity, had no effect on HIF-1 levels and VEGF release. Collectively, these data suggest that carnosine promotes post-ischemic revascularization via augmentation of pro-angiogenic HIF1-/VEGF signaling, possibly by Fe2+ chelation.